(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The article discusses provides information on the benefits of green building construction, construction-related savings including increased employee productivity, reduced health and safety costs, and savings on energy, maintenance and operating costs.